Penetration of Ar and He RF-driven plasma jets into micrometer-sized capillary tubes. (23rd August 2018) - Brahme, Amita; Chang, Zhengshi; Zhao, Ni; Kondeti, V S Santosh K; Bruggeman, Peter J
Abstract: The penetration and propagation of cold atmospheric pressure plasmas into volumes having sub-millimeter to micrometer sizes with large aspect ratios is required for enabling an effective disinfection of the inside of catheter tubes, tooth cavities, skin pores and enhance plasma catalysis in porous catalysts. We report on a study using a low voltage RF driven argon and helium plasma jets with the plasma generation outside a capillary tube with a large aspect ratio followed by its penetration and propagation inside the capillary. We present the experimental determination of the limitations on the penetration diameter, and the underpinning mechanisms of the plasma propagation and penetration process. Experimental results include time resolved imaging of plasma propagation and penetration in capillaries with different internal diameter and surface electric field measurements. We found that the time between the plasma jet in first contact with the capillary tube surface and the subsequent penetration into the capillary tube spans several RF cycles due to electric fields at the plasma-tube interface below 4 kV cm −1 . These low electric fields require Penning ionization and/or stepwise ionization and hence a buildup of the metastable and electron density is required to achieve a sufficiently large ionization rate near the capillary tube inlet to enable penetration and propagation. Furthermore, it is found that the propagation of the argon jet into the capillary occurs during the positive half cycle of the RF waveform and is very similar to the propagation of the jet in surrounding air.